An Enhanced Data Integrity Technique for Cloud Storage with Integrated Archive Using PDP - Saravana Kumar, C; Vijaya Kumar, K (International Journal of Engineering and Technology, 2018)
The cloud storage plays vital role in the recent trend in information technology. Storage in cloud to be efficient and effective with compressed files method but it faces problem which are related to space and time complexity. There are various techniques are available such as ZIP, JAR, and TXT etc with various disadvantages are exits due to incompatible for recovery records, Unicode names, and strong AES encryption. This problem has been addressed byusing some high compressibility ratio capabilities like RAR using WAR technology. It is more convenient of multipart archives, tight compression multimedia, text modes, strong AES encryption, recovery records to repair an archive in case of physical damage to file. It also includes all work that is related to web application like Servlet, XML, JSP, Image, HTML, CSS, and JSetc. The main advantage in WAR file is, it takes less time to transfer the file as it does all web related work at one time. Therefore RAR format using WAR file is used to have the storage of file in cloud which is of more credential than JAR format using ZIP file. The common security issues like confidentiality, integrity, Privacy-Provable Data Possession technique have been applied for better reliability.